(untitled) (Annals of Medical Research, 2023)
Aim: Intravenous immunoglobulin (IVIG), used as an option in the treatment of severe Coronavirus disease 2019 (COVID-19), has been shown to have effects on the suppression of the hyperinflammatory state through immunomodulatory actions. The aim of our study was to evaluate the factors associated with mortality in patients treated with IVIG for COVID-19. Materials and Methods: Patients diagnosed with COVID-19 and receiving IVIG therapy in addition to standard care therapy were included in the study. Results: A total of 46 patients who received IVIG treatment were included in the study. The mortality rate was higher in patients aged over 52 years (p:<0.001). The mortality rate was found to be higher in patients with an interval of more than 7 days between hospitalization and the start of IVIG treatment (p:0.009). Patients with a higher Charlson Comorbidity Index (CCI) score had a more mortal course (p<0.001). Mortality rate was higher in patients with high immunoglobulin A (Ig A) levels before IVIG treatment (p:0.004). Survival rate was lower in patients with high neutrophil lymphocyte ratio (NLR), urea and prothrombin time (PT)and low albumin and lymphocyte counts. Conclusion: A high Charlson Comorbidity Index score and high immunoglobulin A level are poor prognostic in COVID 19 patients treated with IVIG. Studying mortality risk factors is valuable in predicting response to IVIG therapy and may help in early identification of patients with poor prognosis and re-evaluate of treatment strategy.